2014
DOI: 10.1002/maco.201307468
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion resistance of new powder metallurgy boron‐containing stainless steel in the nuclear repository environment

Abstract: The paper studies corrosion resistance of a new type of material in the environment of moist bentonite, which is typical for nuclear waste repository. The material was characterized by measurements of hardness, metallography, and scanning electron microscopy. Methods of impedance spectroscopy, potentiodynamic, and potentiostatic tests were used to assess corrosion resistance. The measurements were carried out in pore solution of Czech bentonite Rokle B75 and model pore solution B1600 of Volclay MX80 bentonite.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…In both boron-containing steels, it can be observed that the formed particles are mainly enriched with Cr and Mn, as shown in Figure 5 . As reported by Stoulil et al [ 62 ], a eutectic system based on (Cr, Fe) 2 B is formed during the manufacturing process of these materials. The formation of a (Fe, Cr) 2 B-based eutectic system also follows from the binary diagrams of the individual components at a particular composition [ 63 ].…”
Section: Resultsmentioning
confidence: 81%
“…In both boron-containing steels, it can be observed that the formed particles are mainly enriched with Cr and Mn, as shown in Figure 5 . As reported by Stoulil et al [ 62 ], a eutectic system based on (Cr, Fe) 2 B is formed during the manufacturing process of these materials. The formation of a (Fe, Cr) 2 B-based eutectic system also follows from the binary diagrams of the individual components at a particular composition [ 63 ].…”
Section: Resultsmentioning
confidence: 81%
“…Další technikou z portfolia elektrochemických metod jsou potenciodynamická měření. Ta jsou používána pro charakterizaci anodického chování kovu, zejména průrazové křivky bodové koroze [4,62,63,70,85] či kinetiku depolarizačních reakcí na povrchu [63]. Jejich obdobou je cyklická voltametrie, která je více vhodná pro sledování katodických reakcí [56,67], ale lze nalézt uplatnění i pro anodické děje [63].…”
Section: Mikrobiální Koroze V Hlubinném úLožištiunclassified
“…It is candidate material for outer case in Scandinavian concept [1][2][3][4][5] and for coating in Canadian [6][7][8][9][10]. Copper is also one of the candidate materials for construction of canisters in Czech concept [11][12][13][14][15][16][17][18]. In previous works we studied the effect of sulphide content on corrosion rate of copper in bentonite pore solution [18] and simulation of galvanic couple with carbon steel [14].…”
Section: Introductionmentioning
confidence: 99%